Effect of the interaction between physical activity and estimated macronutrient intake on HbA1c: population-based cross-sectional and longitudinal studies. Issue 1 (3rd January 2022) - Furukawa, Takuma; Nishida, Yuichiro; Hara, Megumi; Shimanoe, Chisato; Koga, Kayoko; Iwasaka, Chiharu; Higaki, Yasuki; Tanaka, Keitaro; Nakashima, Ryoko; Ikezaki, Hiroaki; Hishida, Asahi; Tamura, Takashi; et al.
Abstract : Introduction: Healthy diet and physical activity (PA) are essential for preventing type 2 diabetes, particularly, a combination of diet and PA. However, reports on interaction between PA and diet, especially from large epidemiological studies, are limited. We investigated the effect of interaction between PA and macronutrient intake on hemoglobin A1c (HbA1c) levels in the general population. Research design and methods: We conducted a cross-sectional study of 55 469 men and women without diabetes who participated in the baseline survey of the Japan Multi-Institutional Collaborative Cohort Study. A self-administered questionnaire ascertained PA and macronutrient intake (carbohydrate, fat, and protein). Multiple linear regression analyses were performed to adjust for confounding variables and examine the interactions. In addition, we conducted a longitudinal study during a 5-year period within a subcohort (n=6881) with accelerometer-assessed PA data. Results: Overall, PA had a weak inverse association (β=−0.00033, p=0.049) and carbohydrate intake had a strong positive association (β=0.00393, p<0.001) with HbA1c. We observed a tendency of interactions between PA and carbohydrate or fat intake, but not protein intake, on HbA1c levels after adjusting for age, sex, study area, total energy intake, alcohol consumption, smoking, and medication for hypertension or hypercholesterolemia (Pinteraction =0.054, 0.006, and 0.156, respectively). The inverse associations between PA and HbA1c level were more evident in participants with high-carbohydrate (or low-fat) intake than in participants with low-carbohydrate (or high-fat) intake. Although further adjustment for body mass index slightly attenuated the above interactions (Pinteraction =0.098 for carbohydrate and 0.068 for fat), the associations between PA and HbA1c level in stratified analyses remained unchanged. Similar associations and interactions were reproduced in the longitudinal study. Conclusions: The present results suggest that the effect of PA on HbA1c levels is modified by intake of macronutrient composition.